Energy Consumption and Efficiency Optimization in Freeze Drying of Fruits and Vegetables: A Review - Zudana, Kirana; Wahyuni, Fitri; Putri, Sheila; Lestari, Yuniar (Journal of Clean Technology, 2025)
Fruits and vegetables are essential for global nutrition and economic growth, yet they are among the most perishable food commodities, contributing to major postharvest losses worldwide. Freeze drying is widely recognized as a superior preservation method that maintains the structural integrity, nutritional value, and sensory quality of fresh produce. Despite its advantages, freeze drying is energy-intensive, posing challenges for cost-effectiveness and sustainability in large-scale applications. This review explores the freeze drying process in detail, highlighting the critical operational parameters such as freezing rate, chamber pressure, shelf temperature, and sample thickness, that influence both product quality and energy consumption. Additionally, the role of cryoprotectants in preserving bioactive compounds during drying is discussed. By identifying optimization strategies for these parameters, this study aims to support the development of more energy-efficient and economically viable freeze drying systems for the fruit and vegetable processing industry.